Radiotherapy for Prostate Cancer: is it 'what you do' or 'the way that you do it'? A UK Perspective on Technique and Quality Assurance. Issue 9 (September 2016) - ; Bonnington, Sue; Bradshaw, Lynne; Cooper, Debbie; Elliott, Emma; Herbert, Pippa; Holding, Peter; Howson, Joanne; Jones, Mandy; Lennon, Teresa; Lyons, Norma; Moody, Hilary; et al.
Abstract: Aims: The treatment of prostate cancer has evolved markedly over the last 40 years, including radiotherapy, notably with escalated dose and targeting. However, the optimal treatment for localised disease has not been established in comparative randomised trials. The aim of this article is to describe the history of prostate radiotherapy trials, including their quality assurance processes, and to compare these with the ProtecT trial. Materials and methods: The UK ProtecT randomised trial compares external beam conformal radiotherapy, surgery and active monitoring for clinically localised prostate cancer and will report on the primary outcome (disease-specific mortality) in 2016 following recruitment between 1999 and 2009. The embedded quality assurance programme consists of on-site machine dosimetry at the nine trial centres, a retrospective review of outlining and adherence to dose constraints based on the trial protocol in 54 participants (randomly selected, around 10% of the total randomised to radiotherapy, n  = 545). These quality assurance processes and results were compared with prostate radiotherapy trials of a comparable era. Results: There has been an increasingly sophisticated quality assurance programme in UK prostate radiotherapy trials over the last 15 years, reflecting dose escalation and treatment complexity. In ProtecT, machine dosimetry results were comparable between trial centres and with the UK RT01 trial. The outlining review showed that most deviations were clinically acceptable, although three (1.4%) may have been of clinical significance and were related to outlining of the prostate. Seminal vesicle outlining varied, possibly due to several prostate trials running concurrently with different protocols. Adherence to dose constraints in ProtecT was considered acceptable, with 80% of randomised participants having two or less deviations and planning target volume coverage was excellent. Conclusion: The ProtecT trial quality assurance results were satisfactory and comparable with trials of its era. Future trials should aim to standardise treatment protocols and quality assurance programmes where possible to reduce complexities for centres involved in multiple trials. Highlights: No randomised evidence defines the optimal treatment for localised prostate cancer. Radiotherapy can be curative for localised disease. Trial quality assurance is necessary with increasing radiotherapy dose and complexity. The ProtecT trial reports on active monitoring, radiotherapy and surgery in 2016.